Psammobiont halacarid mites (Acari: Halacaridae) from Türkiye: description of two new species of the genus Atelopsalis Trouessart, 1896 and Scaptognathus Trouessart, 1889 and two new records - Durucan, Furkan (Zootaxa, 2024)
In this paper, two new species from the genera Atelopsalis Trouessart, 1896 and Scaptognathus Trouessart, 1889 are described from the eastern Mediterranean Sea, off the coast of Antalya, Türkiye. Atelopsalis mediterranea sp. nov. is described based on female, male, and deutonymph specimens collected from soft sand sediment in Kaş, Antalya. Scaptognathus antalyaensis sp. nov. is described based on female and male specimens from soft sediment in Kundu, Antalya. In addition to these new species, two arenicolous halacarid mites, Acarochelopodia delamarei Angelier, 1954 and Anomalohalacarus anomalus (Trouessart, 1894), are reported from the Turkish coasts for the first time. Both psammic halacarid mites were found in medium coarse sand sediment habitats at Örnekköy Beach.